Analisis Perbandingan Hasil Aplikasi Fiber Optic Calculator Dengan Impementasi FTTH Pada OLT EPON HSQG - Ahmad Tantoni; Mohammad Taufan Asri Zaen; Khairul Imtihan (STMIK Budi Darma, 2023)
In the use of fiber optic cables, there are technologies used, including FTTH (Fiber to The Home) technology infrastructure, which is an optical network architecture starting from the central office (STO) to customer devices in every home (end user) [1]. EPON uses a point-to-multipoint architecture and a passive transmission splitter to provide services over Ethernet. EPON does not require complicated protocols, optical signals are transmitted accurately to end users, and data from end users can be transmitted to the central network [2]. The problem in this study when implementing FTTH (Fiber to The Home) network technology infrastructure using OLT EPON hardware requires a good and mature design because when selecting the splitter ratio used, the passive splitter used, the pigtail attenuation, and the attenuation of the patchcore (link power budget) must be considered. If the design and simulation are not carried out properly, there will be a nominal budget that will swell. To avoid the funds exceeding budget, design and simulation is carried out using the Fiber Optic Calculator Application so that there is an idea of the splitter ratio value and the passive splitter value to be used. This is expected to be a solution to the problem of selecting the value of the splitter ratio and the passive splitter used. This study aims to compare the values of the magnitude of the splitter and passive splitter ratios used when simulating the Fiber Optic Calculator application with real implementation on the OLT EPON HSQG network hardware